Epilepsy or Eclampsia in Differential Diagnosis of Recurrent Seizures in Pregnancy Aisyiyah Bojonegoro Hospital: A Diagnostic Dilemma? A Case Report - Khaidar, Reyfal; Fitri, Wafa Sofia; Sania, Hen; Rahman, Mafida Wida; Modjo, Annisa Afiyatushsholihah; Subiantoro, Andri; Indriani, Ratri Dwi; Zammara, Abdurrahman; Ridho, Muhammad Ainur Rosyid (Journal of Medicine and Health Technology, 2024)
Seizures in pregnancy can lead to adverse maternal and perinatal outcomes, often arising from various factors necessitating clear diagnosis for effective therapy. Concurrent occurrence of multiple causative factors can complicate diagnostic and therapeutic decisions. We present a case of a 32-week pregnant woman with poorly managed epilepsy who experienced eclampsia and recurrent seizures. Treatment involved multiple medications and emergency cesarean delivery with meticulous blood pressure control. Close monitoring and therapy adjustment were crucial. Managing seizures in such cases poses a dilemma, necessitating initial focus on airway, breathing, and circulation stabilization. Immediate delivery of a viable fetus and maternal health maintenance are paramount. Anesthetic goals encompass seizure and blood pressure control, hemodynamic stability, and intensive care support for potential complications. While eclampsia is a significant factor, seizures in pregnancy may arise from diverse causes, demanding early diagnosis and tailored treatment for optimal patient outcomes.